EFFECT OF WATER RESTRICTION ON BODY WEIGHT, FEED INTAKE AND PHYSIOLOGICAL RESPONSES IN BARBARI GOATS1 - MAURYA, C. M.; LAKHANI, G. P.; GHOSH, S.; ROY, B.; JAIN, A. (Indian Journal of Animal Production and Management, 2017)
ABSTRACT Total of 18 Adult female Barbari goats of identical body weight and size were selected to study the effect of water restriction on body weight, feed intake and physiological responses. The goats were distributed randomly in three different groups of 6 in each and assigned three different treatments: control (T1), 15 % water restriction (T2) and 30 % water restriction (T3). All the goats were stall fed on concentrate and gram straw. Study was conducted in two phases, 30 days in each phase (January and April) for total 60 days. The body weight reduced by 3.89% when goats are kept in 15% water restriction (T2) and 9.28% when goats kept on 30% water restriction (T3) compared to control group (T1). The dry matter intake was reduced by 8.01% when goats are kept in 15% water restriction (T2) and 19.06% when goats kept on 30% water restriction (T3) compared to control group (T1). There was significant effect of water restriction both at 15% and 30% levels on pulse rate and at 30% level on rectal temperature. But, water restriction had no significant effect on respiration rate. Therefore, 15% water restriction is possible in goat without much affecting its performance. Keywords: Barbari goats, water restriction, dry matter, bodyweight, pulse rate, respiration rate, and rectal temperature.